Bridging the Gap Between Vessels and Nerves in Fabry Disease - Forstenpointner, Julia; Sendel, Manon; Moeller, Paul; Reimer, Maren; Canaan-Kühl, Sima; Gaedeke, Jens; Rehm, Stefanie; Hüllemann, Philipp; Gierthmühlen, Janne; Baron, Ralf (Frontiers in Neuroscience, 2020)
Purpose: Fabry disease frequently includes pain as an early disease feature, which was characterized as a dysfunctional processing of somatosensory information in various studies. The pathomechanism involves the mutation in the x-chromosomal GLA-gene and a consequent reduction of the alpha-galactosidase. This results in an insufficient reduction of globotriaosylceramide (GL3). Interestingly, an accumulation of GL3 was shown in both vascular endothelial cells as well as nerve tissue. This implicates that both an endothelial as well as nerve dependent dysfunction may be considered as prominent mechanisms in pain pathogeneses. Patients and Methods: The exploration of endothelial and C-fiber dependent microcirculatory changes was conducted in a healthy cohort (n=22), in patients with polyneuropathy (n=21) and Fabry disease (n=15). Microcirculatory measurements were conducted using a laser-speckle-contrast-analysis (LASCA) in combination with a thermoprobe controlling system, which applied a constant heat stimulus (42°C). Additionally, nerve fiber function was assessed via Quantitative Sensory Testing and heart rate variability. Results: The results indicated a characteristic perfusion profile in the control group as well as both patient groups. Fabry patients had the smallest increase of endothelial dependent perfusion as compared to the others (% increase as compared to Fabry: control +129% [p=0.002], PNP +126% [p=0.019]). The sensory testing indicated a dysfunctional processing of A-delta fibers in Fabry disease as compared to healthy controls (CDT: p=0.004, MPT: p=0.007) and PNP patients (MPT: p=0.001). Conclusion: Our results point to both an endothelial as well as nerve dependent dysfunction in Fabry disease. Therefore, not only direct changes in nerve fiber tissue may contribute to an altered sensory processing. Indeed, evidence of a perfusion change in vasa nervorum could also contribute to the dysfunctional processing of sensory information, which likely occurs under physical stress.